Mekanisme Keruntuhan Fondasi Tiang Helical Tunggal Pada Tanah Gambut Secara Numerik Menggunakan Model Soft Soil Creep - Fadel Muhammad; Syawal Satibi; Ferry Fatnanta (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Peat is spread widely in Sumatera Island, especially in Riau Province, Indonesia. Peat is included as problematic soil because it has low bearing capacity. The use of helical pile foundation on peat is one of the innovations to increase the peat’s bearing capacity. In this research, numerical modelling of single helical pile foundation load test on peat were carried out, based on the full-scale test conducted by Suratman (2019). The modelling were done by using PLAXIS 2D 2016 program with Axisymetry model type, with the Soft Soil Creep (SSC) soil model. This modelling aimed to know the failure mechanism of model. The parameters used in the modelling were obtained from laboratory test data and field tests and also from trial and error method. The failure mechanism that occurs on the Soft Soil Creep (SSC) model is more likely to be a cylindrical shear failure.Keywords : Peat, Helical Pile, PLAXIS 2D, Failure Mechanism.